2009
DOI: 10.1158/0008-5472.can-08-3382
|View full text |Cite
|
Sign up to set email alerts
|

DDB1 Targets Chk1 to the Cul4 E3 Ligase Complex in Normal Cycling Cells and in Cells Experiencing Replication Stress

Abstract: The Chk1 protein kinase preserves genome integrity in normal proliferating cells and in cells experiencing replicative and genotoxic stress. Chk1 is currently being targeted in anticancer regimens. Here, we identify damaged DNA-binding protein 1 (DDB1) as a novel Chk1-interacting protein.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
142
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(150 citation statements)
references
References 54 publications
8
142
0
Order By: Relevance
“…These results suggest that SFKs are capable of suppressing ATR-mediated Chk1 phosphorylation via a mechanism other than Claspin degradation. Although we did not investigate whether SFK inhibition perturbs Chk1 dephosphorylation or degradation (25)(26)(27)(28)(29)(30), these data suggest that SFKs regulate ATR signaling via ATRdependent Rad17 phosphorylation.…”
Section: Sfk Activity Is Required For G 2 Dna Damage Checkpointmentioning
confidence: 84%
See 1 more Smart Citation
“…These results suggest that SFKs are capable of suppressing ATR-mediated Chk1 phosphorylation via a mechanism other than Claspin degradation. Although we did not investigate whether SFK inhibition perturbs Chk1 dephosphorylation or degradation (25)(26)(27)(28)(29)(30), these data suggest that SFKs regulate ATR signaling via ATRdependent Rad17 phosphorylation.…”
Section: Sfk Activity Is Required For G 2 Dna Damage Checkpointmentioning
confidence: 84%
“…Claspin mediates the ATR-dependent phosphorylation of Chk1 to activate the ATR-Chk1 signaling pathway (20). Following checkpoint activation, several protein phosphatases and ubiquitin ligases target the activated checkpoint proteins including Rad17 (21), Claspin (22)(23)(24), and Chk1 (25)(26)(27)(28)(29)(30). The direct dephosphorylation and degradation of checkpoint proteins promote the termination of checkpoint signaling (1)(2)(3).…”
mentioning
confidence: 99%
“…Previous studies have shown that Chk1 is degraded by the ubiquitinproteasome system and that this can be stimulated by phosphorylation of the protein at S345 (18)(19)(20)(21)(22). Because we had observed a decrease in phospho-Chk1 at earlier time points after Atg7 recombination, we reasoned this may be due to enhanced degradation of the protein, which over time would then have an impact on the total pool of Chk1 under conditions where DNA-damage signaling would be enhanced after a prolonged loss of autophagy.…”
Section: Significancementioning
confidence: 84%
“…Although we did observe DNA damage 3 days after And-1 depletion, we did not observe DNA damage in cells harvested 48 h after siRNA transfection (Supplementary Fig S3D). Given that DNA damage itself can induce Chk1 protein degradation (Zhang et al, 2005(Zhang et al, , 2009Leung-Pineda et al, 2009), it is possible that the degradation of Chk1 that was observed by Yoshizawa-Sugata et al resulted from DNA damage due to an extended period of And-1 depletion.…”
Section: Discussionmentioning
confidence: 99%